PROPOSAL FOR IMPROVEMENT IN THE SETTING PROCESS IN THE BROTH TREATMENT OF A SUGAR AND ETHANOL PLANT - da Silva, David Gonçalves; Rodolpho, Daniela (Revista Interface Tecnológica, 2022)
In continuous processes, variability is a major challenge for good performance. This article addresses the identification of a problem of instability in the decanting process in the juice treatment sector of a sugarcane plant and the application of an automatic operation equipment that solves this problem. The purpose of the proposal was to reduce procedural instability and, through success, achieve economy of inputs. Therefore, using quality tools, through the Ishikawa Diagram, it made it possible to identify the root cause and, through the PDCA cycle, the application of the new equipment in a clear, effective and efficient way. This project generated numerous benefits due to the fact of stability, because by reducing variability, it is gained with the increase in standardization in the processes, such as the specification of the final product and the operational one. Therefore, this impact considerably affects other sectors, such as finance, due to the economy in the dosage of products.